Analisa Rugi-Rugi Serat Optik Menggunakan Optical Time Domain Reflectometer Dengan Aplikasi AQ77932 Emulation - ., Fazra Habib (Jurnal Teknik Elektro Universitas Tanjungpura, 2015)
ABSTRACT Optical fiber media have more reliability for optical fiber capable of delivering the data with a large capacity. Besides speed fiber optic data transfer media may reach 200.000 Mbps (200 Gbs), optical fiber communication systems inseparable from the influence of losses that affect the performance of optical fiber. Losses basically can be affect the Performance of an optical fiber communication system, but the size of the influence losses can be seen by conducting measurements performed that using Yokogawa OTDR AQ 7275 and compared with the results of standardized calculation using the power link budget calculation method. Based on the results of the comparison between the results of measurements and calculations it can be seen the performance of optical fibers. It can be done by performing measurements and calculations in the Pontianak-Sungai Raya link and link-GI GCC. Thus obtained cores with a value of large losses on the link GCC-GI located in the core 9 which has the value 31.261 dB losses which are at a distance 6.4957 km. Losses occurred due to losses macrobending so necessary improvement measures to establish the connection (splicing). Loss of value of measurement results and calculations of optical fiber communication systems from Pontianak-Sungai Raya link and link-GI GCC in PT.Telkom still in good shape and had a good Performance of the average, based on the measurement values are still below the value calculation. Keywords: Fiber Optics, Losses, Splicing, Power Link Budget